2021
DOI: 10.3390/jcm10194625
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis Burden of Missed and Added Populations According to the New Definition of Metabolic Dysfunction-Associated Fatty Liver

Abstract: Recently, the classification of fatty liver and the definition for non-alcoholic fatty liver disease (NAFLD) have been challenged. Herein, we aim to evaluate the burden of hepatic fibrosis in the missed and added populations following the proposal of the new definition of metabolic dysfunction-associated fatty liver (MAFLD) in a health check-up cohort. A total of 6775 subjects underwent both magnetic resonance elastography (MRE) and an abdominal ultrasound at 13 nationwide health check-up centers in Korea. Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The global burden of NAFLD is on the rise with the increasing prevalence of obesity [1,3,4]. Nonalcoholic steatohepatitis (NASH) is a progressive form of NAFLD that occurs in close association with obesity, type 2 diabetes, and metabolic syndrome [3,5,6]. No approved pharmacological options are currently available for patients with NASH; therefore, the demand for developing new therapeutic agents is still high.…”
Section: Introductionmentioning
confidence: 99%
“…The global burden of NAFLD is on the rise with the increasing prevalence of obesity [1,3,4]. Nonalcoholic steatohepatitis (NASH) is a progressive form of NAFLD that occurs in close association with obesity, type 2 diabetes, and metabolic syndrome [3,5,6]. No approved pharmacological options are currently available for patients with NASH; therefore, the demand for developing new therapeutic agents is still high.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the usefulness of imaging examinations such as computed tomography (CT) and magnetic resonance (MR) imaging for noninvasively evaluating liver fibrosis [ 1 , 2 , 3 , 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Hepatic extracellular volume fraction (fECV) analysis with contrast-enhanced CT is another noninvasive method for evaluating liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…MAFLD is known to be better at stratifying those at a higher risk for advanced liver fibrosis and overall mortality than the previous NAFLD definition. 2 - 4 Due to the exclusive nature of the NAFLD definition, we could not call comorbid hepatic steatosis as NAFLD when it co-exists with viral hepatitis, for example. However, MAFLD includes those patients with other chronic liver diseases permitting dual etiologies in a same patient.…”
mentioning
confidence: 99%